Intrathecal dexmedetomidine versus magnesium sulfate as adjuvant to hyperbaric bupivacaine in total abdominal hysterectomy - Abeer E Farhat; Mona E Elkafrawy (Wolters Kluwer Medknow Publications, 2020)
Background Different adjuvants have been added to local anesthetics to increase the duration of regional anesthesia, delay onset of postoperative pain, and decrease pain-relieving drugs. The present study aims to compare the effect of adding dexmedetomidine versus magnesium sulfate to intrathecal hyperbaric bupivacaine in total abdominal hysterectomy regarding onset, duration of sensory and motor blockade, duration of postoperative analgesia, hemodynamic stability, and complications. Patients and methods A prospective randomized double-blind clinical study included 40 women aged 40-56 years, with American Society of Anesthesiologists physical status I and II, scheduled for total abdominal hysterectomy. They were randomly divided into two groups: group I (n=20) got 15 mg of 0.5% hyperbaric bupivacaine in addition to 10 μg dexmedetomidine, whereas group II (n=20) got 15 mg of 0.5% hyperbaric bupivacaine in addition to 100-mg magnesium sulfate, in a total volume of 4 ml in both groups. The primary outcome is onset, duration, and intensity of sensory and motor blockade. The secondary outcomes are hemodynamic stability, duration of postoperative analgesia, and complications. Results The onset of sensory and motor blockade was significantly faster and of prolonged duration in dexmedetomidine group than magnesium sulfate group (P<0.001). The duration of postoperative analgesia was significantly prolonged in dexmedetomidine group (P<0.001). Regarding hemodynamic and complications, there were no significant differences between both groups (P˃0.005). Conclusion Addition of dexmedetomidine to intrathecal bupivacaine appears to be superior to magnesium sulfate as it produce faster onset and prolongs the duration of sensory and motor blockade and postoperative analgesia.